E-construction waste exchange in Malaysia: a preliminary study - Nasaruddin, F.H.M.; Ramli, N.H.M.; Ravana, S.D. (2008)
As a developing country, Malaysia is no exception in facing construction waste management issues. Since demand of new, construction project increases every year, construction waste dump at landfill has also increased at an alarming rate. In this preliminary study, current construction waste situation and construction waste exchange system are studied Representative from Institute for Environmental and Development, LESTARI and Construction Industry Development Board of Malaysia (CIDB) were interviewed, and a survey has was carried out to understand contractors and developers view of construction waste management. As a result, econWasteExchange model has been developed and targeted users are contractors, developers, local council and Construction Industry Development Board of Malaysia (CIDB).